Ketoprofen Associated with Hyaluronic Acid Hydrogel for Temporomandibular Disorder Treatment: An In Vitro Study - Miranda, Diego Garcia [UNESP]; Ramos, Lucas de Paula; Lopes, Nicole Fernanda dos Santos [UNESP]; Silva, Nicole Van Der Heijde Fernandes [UNESP]; Soares, Cristina Pacheco; Rodrigues, Flavia Pires; Morais, Vinicius de Paula; Sani-Taiariol, Thalita; Baldan, Mauricio Ribeiro; Vasconcellos, Luana Marotta Reis de [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; Grosgogeat, Brigitte; et al. (MDPI, 2024)
Temporomandibular disorders (TMD) are a public health problem that affects around 12% of the global population. The treatment is based on analgesics, non-steroidal anti-inflammatory, corticosteroids, anticonvulsants, or arthrocentesis associated with hyaluronic acid-based viscosupplementation. However, the use of hyaluronic acid alone in viscosupplementation does not seem to be enough to regulate the intra-articular inflammatory process. So, we propose to develop and evaluate the physicochemical and biological properties in vitro of hyaluronic acid hydrogels (HA) associated with ketoprofen (KET) as a new therapeutic treatment for TMD. The hydrogels were synthesized with 3% HA and 0.125, 0.250, 0.500, or 1% KET. Physicochemical analyses of Attenuated Total reflectance-Fourier transform infrared spectroscopy (FTIR), Thermogravimetry (TGA), Rheology by Frequency, Amplitude sweeps, temperature ramp, and scanning electron microscopy (SEM) were performed with or without sterilization and cycled. Cytocompatibility and genotoxicity (micronucleus assay) were performed in mouse macrophages (RAW 264-7) for 24 h. Results: FTIR spectrum showed characteristic absorptions of HA and KET. In the TGA, two mass loss peaks were observed, the first representing the water evaporation at 30 and 100 °C, and the second peaks between 200 and 300 °C, indicating the degradation of HA and KET. Rheology tests in the oscillatory regime classified the hydrogels as non-Newtonian fluids, time-dependent, and thixotropic. Mouse macrophages (RAW 264-7) presented viability of 83.6% for HA, 50.7% for KET, and 92.4%, 66.1%, 65.3%, and 87.7% for hydrogels, in addition to the absence of genotoxicity. Conclusions: Hyaluronic acid associated with ketoprofen shows satisfactory physicochemical and biological properties for use as viscosupplementation. As a limiting point of this study, further research is needed to evaluate the pharmacodynamic, toxicological, and pharmacokinetic characteristics of a complete organism.
Keywords: non-steroidal anti-inflammatory agents 1; osteoarthritis 3; polysaccharides 2